2021
DOI: 10.3390/mi12010094
|View full text |Cite
|
Sign up to set email alerts
|

Micropatterning of Substrates for the Culture of Cell Networks by Stencil-Assisted Additive Nanofabrication

Abstract: The fabrication of in vitro neuronal cell networks where cells are chemically or electrically connected to form functional circuits with useful properties is of great interest. Standard cell culture substrates provide ensembles of cells that scarcely reproduce physiological structures since their spatial organization and connectivity cannot be controlled. Supersonic Cluster Beam Deposition (SCBD) has been used as an effective additive method for the large-scale fabrication of interfaces with extracellular matr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Furthermore, these nanotopographical surfaces have been tested and validated as micropatterned substrates on a neuronal-like cell line (PC12), CA3-CA1 primary hippocampal neurons and astrocytes. For the neuronal cells, it has been shown that they grow and differentiate in a confined manner in these nanostructured zirconia micropatterns [32,33]. For astrocytes, so far the effective confinement of astrocytes in a nanostructured zirconia pattern has also been demonstrated in Ref.…”
Section: Introductionmentioning
confidence: 93%
See 4 more Smart Citations
“…Furthermore, these nanotopographical surfaces have been tested and validated as micropatterned substrates on a neuronal-like cell line (PC12), CA3-CA1 primary hippocampal neurons and astrocytes. For the neuronal cells, it has been shown that they grow and differentiate in a confined manner in these nanostructured zirconia micropatterns [32,33]. For astrocytes, so far the effective confinement of astrocytes in a nanostructured zirconia pattern has also been demonstrated in Ref.…”
Section: Introductionmentioning
confidence: 93%
“…The fabrication of micrometric patterns for the confined culture of astrocytes involved the functionalisation of glass coverslips with an antifouling molecule, PAcrAm-g-(PMOXA, NH2, Si, produced by SuSoS AG 151-Dubendorf, Switzerland), and the subsequent fabrication of a nanostructured zirconia (ZrO x ) coating via supersonic cluster beam deposition (SCBD), according to a specific micrometric pattern. The detailed protocol for the substrate cleaning and antifouling functionalisation is described in [33]; here, we briefly describe the experimental details of nanostructured pattern deposition.…”
Section: Fabrication Of Micropatterned Nanostructured Substratesmentioning
confidence: 99%
See 3 more Smart Citations